First record of larvae of the water mite Hydrachna processifera Piersig, 1895 from Turkey (Acari, Hydrachnidia, Hydrachnidae) - Aykut, Medeni; Zawal, Andrzej; Esen, Yunus; Erman, Orhan (Pensoft Publishers, 2018)
Larvae of water mite Hydrachna processifera Piersig, 1895 (Acari, Hydrachnidiae) were reported on diving beetles Dytiscus marginalis Linnaeus, 1758 (Coleoptera, Dytiscidae) from Turkey. The redescription of the larva was made. Earlier, the larva H. processifera was described as H. inermis, but it was subsequently synonymized with H. processifera. The larva of H. processifera is a new record for the Turkish fauna. All larvae of H. processifera were found on the mesosternum of the one specimens (prevalence = 16.7%).
Keywords: Dytiscus marginalis; Hydrachna inermis; parasitism; water beetles; water mites